Characterization of a bifunctional alginate lyase as a new member of the polysaccharide lyase family 17 from a marine strain BP-2 - Huang, Guiyuan (Biotechnol Lett, 2019)
OBJECTIVES: Bifunctional alginate lyase can efficiently saccharify alginate biomass and prepare functional oligosaccharides of alginate. RESULTS: A new BP-2 strain that produces alginate lyase was screened and identified from rotted Sargassum. A new alginate lyase, Alg17B, belonging to the polysaccharide lyase family 17, was isolated and purified from BP-2 fermentation broth by freeze-drying, dialysis, and ion exchange chromatography. The enzymatic properties of the purified lyase were investigated. The molecular weight of Alg17B was approximately 77 kDa, its optimum reaction temperature was 40–45 °C, and its optimum reaction pH was 7.5–8.0. The enzyme was relatively stable at pH 7.0–8.0, with a temperature range of 25–35 °C, and the specific activity of the purified enzyme reached 4036 U/mg. A low Na(+) concentration stimulated Alg17B enzyme activity, but Ca(2+), Zn(2+), and other metal ions inhibited it. Substrate specificity analysis, thin-layer chromatography, and mass spectrometry showed that Alg17B is an alginate lyase that catalyses the hydrolysis of sodium alginate, polymannuronic acid (polyM) and polyguluronic acid to produce monosaccharides and low molecular weight oligosaccharides. Alg17B is also bifunctional, exhibiting both endolytic and exolytic activities toward alginate, and has a wide substrate utilization range with a preference for polyM. CONCLUSIONS: Alg17B can be used to saccharify the main carbohydrate, alginate, in the ethanolic production of brown algae fuel as well as in preparing and researching oligosaccharides.